DESIGN OF RETRIBUTION ACCOUNTING INFORMATION SYSTEMS IN MARDIKA MARKET - Shella Kriekhoff (Pusat Riset dan Inovasi Nasional, 2023)
The goal of this study is to create a web-based payment accounting information system that meets the needs of the Ambon Mardika Market Company in order to overcome the shortcomings of the manual registration system. This is a developmental study utilising a qualitative methodology. The research subject is the market payment information system, and the research aim is the Mardika Market Company. Data is gathered through interviews, documentation, and observation. The system development life cycle is used in this study, with the steps of system analysis, system requirements analysis, and system feasibility analysis. Database modelling with database tables, process modelling with flowcharts, and user interface modelling with form design, input design, and output design are all part of system design. Design of a sales accounting information system using MySQL and PHP software. The new architecture is believed to enable more automatic and precise recording and computation, hence supporting the Mardika Regional Market Company's performance continuity.